2018
DOI: 10.16965/ijar.2018.358
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Variations of Nutrient Foramen of Ulna in Saurashtra Region With Its Clinical Relevance

Abstract: Background: Nutrient foramen is an opening into shaft of Ulna which gives passage to the blood vessels of medullary cavity. The knowledge of nutrient foramen is important in surgical procedures like bone grafting and more recently in microsurgical vascularized bone transplantation.Objective: To determine the number, location and direction of nutrient foramen and whether the nutrient foramens obey the rule of ossification, that is directed away from the growing end of the bone or not.Method: The present study c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
2
2
1
Order By: Relevance
“…In the present paper, 89.67% (139 ulnas) had a single NF, 1.94% (3 ulnas) had a double NF, and 8.39% (13) of ulnas had no NF. Our single NF results are closer to the results of Kumari et al (15) and the double NF results of this study are compatible with the findings of Chavda et al (14). Nevertheless, our results of the absence of NF are not consistent with the results of previous studies, and this inconsistency may be due to the difference in sample size and ethnicity.…”
Section: The Number Of Nutrient Foraminasupporting
confidence: 74%
See 2 more Smart Citations
“…In the present paper, 89.67% (139 ulnas) had a single NF, 1.94% (3 ulnas) had a double NF, and 8.39% (13) of ulnas had no NF. Our single NF results are closer to the results of Kumari et al (15) and the double NF results of this study are compatible with the findings of Chavda et al (14). Nevertheless, our results of the absence of NF are not consistent with the results of previous studies, and this inconsistency may be due to the difference in sample size and ethnicity.…”
Section: The Number Of Nutrient Foraminasupporting
confidence: 74%
“…Chavda et al ( 14) stated that 63.76% of NFs were in the middle third (type 2) of the ulna, 22.15% were in the upper third of the ulna and 14.09% were in the lower third of the bones. They also mentioned that the mean FI was 35.34% (14). Similar to the study of Ukoha et al ( 4), Azizi and Danish (1) indicated that most of the NF (80%) were located in the middle third, while the remaining (20%) were situated in the upper third of the ulna.…”
Section: Direction and Topography Of The Nutrient Foramensupporting
confidence: 68%
See 1 more Smart Citation
“…In the ulna we examined, the most common anatomic location of the NF was the anterior surface, as in previous studies (20,(24)(25)(26). While there are studies indicating the NF in the anterior border and medial surface of the ulna, we did not encounter the NF in the anterior border and medial surface in our study (27)(28)(29).…”
Section: Discussioncontrasting
confidence: 52%
“…Similar to the results in the literature, all of the NF in the ulna we examined in the present study were proximally directed. Furthermore, another study reported that it was directed distally and horizontally (20,(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%